Population-based incidence of all-cause anaphylaxis and its development over time: a systematic review and meta-analysis - Pühringer, Vanessa; Jilma, Bernd; Herkner, Harald (Frontiers in Allergy, 2023)
Introduction: It is extremely difficult to compare studies investigating the frequency of anaphylaxis making it challenging to satisfactorily assess the worldwide incidence rate. Using a systematic review and meta-analysis, this publication aims to determine the current incidence of all-cause anaphylaxis worldwide. Additionally, we investigated whether the incidence of anaphylaxis has changed over time and which factors influence the rates determined by individual studies. Methods: A literature search was performed in four databases. All articles that reported relevant information on populationbased incidence rates of all-cause anaphylaxis were included. The protocol was published on INPLASY, the International Platform of Registered Systematic Review and Meta-analysis Protocols. Results: The database query and screening process resulted in 46 eligible articles on anaphylaxis. The current incidence worldwide was found to be approximately 46 cases per 100,000 population per year (95% CI 21-103). Evaluating confounding factors showed that studies using allergy clinics and hospitalizations as data source result in comparably low rates. Moreover, children are less prone to develop anaphylaxis compared to the general population. Using a random effects Poisson model we calculated a yearly increase of anaphylaxis incidence by 7. p<0.05). Discussion: This seems to be the first approach to analyze every reported all-cause anaphylaxis incidence rate until 2017 for an at most accurate determination of its epidemiology. Based on these results, future research could investigate the underlying causes for the rising incidence in order find ways to decrease the condition's frequency.